Pengaruh Current Ratio, Inventory Turnover, Debt to Equity Ratio dan Net Profit Margin terhadap Pertumbuhan Laba (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019) - Nur Kamilah; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to observe the effect of current ratio, inventory turnover, debt to equity ratio and net profit margin partially towards the corporate earnings growth. The population of this research was industrial sector of consumer goods listed in Indonesia Stock Exchange 2016-2019 period. The sample of this research was taken using purposive sampling technique. From the population of 53 companies obtained 10 companies as samples with a research period of four years (2016-2019). Data analysis technique in this research is Multiple Linear Regression Analysis. The result of this research shows that the effect of Current Ratio (CR) was positive but was not significantly effect on earnings growth, Inventory Turnover (ITO) was negative and has no significant effect on earnings growth, while Debt to Equity Ratio (DER) and Net Profit Margin (NPM) have a positive and significant effect on earnings growth.Keywords: Current Ratio (CR), Inventory Turnover (ITO), Debt to Equity Ratio (DER), Net Profit Margin (NPM), Earnings Growth.